2019
DOI: 10.1002/cbdv.201900428
|View full text |Cite
|
Sign up to set email alerts
|

HPLC‐DAD Analysis, Antioxidant and Protective Effects of Tunisian Rhanterium suaveolens against Acetamiprid Induced Oxidative Stress on Mice Erythrocytes

Abstract: The present study was performed to assess the HPLC-DAD analysis as well as antioxidant and protective effects of Tunisian Rhanterium suaveolens (Rs) against acetamiprid (ACT) induced oxidative stress on mice erythrocytes. The in vitro assays showed that the methanolic extract of Rs has an impressive antioxidant effect proved by testing the total antioxidant and scavenging activities using BCB, DPPH and ABTS assays, respectively. Moreover, qualitative and quantitative analysis using HPLC-DAD revealed the richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…First, the methanolic extract of R. suaveolens was obtained as described in detail in Section 3 and in a previous paper. 18 Then, it was added, drop by drop and under stirring conditions, to the solution of AuCl 4 − ions. Initially, the HAuCl 4 solution had a pale yellow color and a pH of 4.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the methanolic extract of R. suaveolens was obtained as described in detail in Section 3 and in a previous paper. 18 Then, it was added, drop by drop and under stirring conditions, to the solution of AuCl 4 − ions. Initially, the HAuCl 4 solution had a pale yellow color and a pH of 4.5.…”
Section: Resultsmentioning
confidence: 99%
“…The profile of these phenolic compounds has been reported in a previous paper. 18 Some of these, such as pcoumaric acid and ferulic acid, are present in high amounts and can act as reducing and stabilizing agents during the synthesis of AuNPs. 19 AuNPs play a key role in the recent advances in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In another study investigating the antioxidant and protective effects of Rhanterium suaveolens on mouse erythrocytes against acetamiprid (ACT)-induced oxidative stress, significant increases in SOD, CAT, and GPx activities were found in mice treated with R. suaveolens at a dose of 300 mg/kg. HPLC-DAD analysis showed that one of the main compounds of the extract was apigenin 7-glucoside and this compound can affected the activity positively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herbarium voucher specimen (number: 155/2019) was deposited at the Faculty of Science (Sfax, Tunisia). The methanolic extracts from Rs flowers, stems and leaves were prepared as previously described by Chelly et al [12] …”
Section: Methodsmentioning
confidence: 99%
“…Although, the extracts from the whole aerial part of Rhanterium suaveolens (Rs) was already studied, [9,12] to the best of our knowledge no study has been carried out on those obtained from different Rs organs (flowers, stems, and leaves).…”
Section: Introductionmentioning
confidence: 99%